2020
DOI: 10.1038/s41467-019-14111-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic changes of HER2-positive breast cancer during and after dual HER2 blockade

Abstract: The HER2-enriched (HER2-E) subtype within HER2-positive (HER2+) breast cancer is highly addicted to the HER2 pathway. However, ∼20-60% of HER2+/HER2-E tumors do not achieve a complete response following anti-HER2 therapies. Here we evaluate gene expression data before, during and after neoadjuvant treatment with lapatinib and trastuzumab in HER2+/HER2-E tumors of the PAMELA trial and breast cancer cell lines. Our results reveal that dual HER2 blockade in HER2-E disease induces a low-proliferative Luminal A phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 41 publications
10
57
2
Order By: Relevance
“…8). Unlike what has been reported previously 30 , conversion to normal-like was not associated with pCR (34.2% vs 33.3%), and conversion to luminal A was infrequent, suggesting that the addition of endocrine therapy may have driven this conversion in the previous study 35 . Integrative subtype was more stable than intrinsic subtype across targeted therapy, perhaps due to it being less dependent on microenvironmental composition: integrative subtype changed in 25.8% of tumors (vs 53.9% for intrinsic subtype; χ2 p = 2.4e-4), with 82.6% of these converting to integrative subtype 9 (IC9, likely misclassification of lower cellularity tumors) ( Fig.…”
Section: Resultscontrasting
confidence: 74%
“…8). Unlike what has been reported previously 30 , conversion to normal-like was not associated with pCR (34.2% vs 33.3%), and conversion to luminal A was infrequent, suggesting that the addition of endocrine therapy may have driven this conversion in the previous study 35 . Integrative subtype was more stable than intrinsic subtype across targeted therapy, perhaps due to it being less dependent on microenvironmental composition: integrative subtype changed in 25.8% of tumors (vs 53.9% for intrinsic subtype; χ2 p = 2.4e-4), with 82.6% of these converting to integrative subtype 9 (IC9, likely misclassification of lower cellularity tumors) ( Fig.…”
Section: Resultscontrasting
confidence: 74%
“…The PAMELA trial found that dual HER2 blockade led to a decrease in CCND1 mRNA in HER2+/HR+ breast tumors (experimental arm), suggesting that the combination therapy was more efficient at arresting the cell cycle and preventing tumor growth in patients with BC. 22 Our study also discovered an association between insurance type and outcome; patients using government-provided insurance exhibited OS, when compared with patients using other types of insurance coverage. While these findings are likely a product of multiple sociodemographic and/or socioeconomic factors and require further exploration, they appear consistent with previously reported literature suggesting that patients with Medicaid had higher mortality rates than privately insured patients following colorectal cancer surgery, 23 and that primary payer status affects patient mortality for most major cancer surgical operations.…”
Section: Breast Cancer: Basic and Clinical Researchsupporting
confidence: 56%
“…All the animal experiments were performed in accordance with the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health and regulations for Laboratory Animal Science Center, Fudan University which include items for the welfare of the animals. Each 6-week-old male BALB/c nude mice (n=5) was injected subcutaneously with a total of 1×10 6 Lentivirus-infected MDA-MB-231 cells suspended in Matrigel (volume, 1:1; Corning, Inc., 356234, NY, USA). 28 days later, mice were euthanized and sections of tumor xenografts were dissected and weighed.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…2,3 Breast cancer is a heterogeneous disease that can be classified into several subtypes based on histological characteristics and the expression of genetic markers. 4 Despite recent advances in breast cancer therapy, including chemotherapy, endocrine therapy, and HER2-targeted therapies, [5][6][7] the high proliferative, invasive, metastatic potential of breast cancer cells, as well as the development of drug resistance, are major causes of therapeutic failure and poor survival in patients with breast cancer. 8,9 Therefore, the development of novel therapeutic approaches is an urgent need.…”
Section: Introductionmentioning
confidence: 99%